2002
DOI: 10.1074/jbc.m205303200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies to Understand the Progressive Development of Resistance in Human Immunodeficiency Virus Type 1 Reverse Transcriptase to Abacavir

Abstract: Abacavir has been shown to select for multiple resistant mutations in the human immunodeficiency type 1 (HIV-1) pol gene. In an attempt to understand the molecular mechanism of resistance in response to abacavir, and nucleoside analogs in general, a set of reverse transcriptase mutants were studied to evaluate their kinetics of nucleotide incorporation and removal. It was found that, similar to the multidrug-resistant mutant reverse transcriptase (RT) Q151M, the mutations L74V, M184V, and a triple mutant conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 75 publications
3
51
0
Order By: Relevance
“…The differences in K d (app) values are in good agreement with enzyme kinetic measurements that point to decreases in K d and K m values with the Y115F mutant (21,22). The Y115F mutation is seen, infrequently, in conjunction with M184V in isolates of patients treated with abacavir (9,23).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The differences in K d (app) values are in good agreement with enzyme kinetic measurements that point to decreases in K d and K m values with the Y115F mutant (21,22). The Y115F mutation is seen, infrequently, in conjunction with M184V in isolates of patients treated with abacavir (9,23).…”
Section: Discussionsupporting
confidence: 70%
“…The Y115F mutation is seen, infrequently, in conjunction with M184V in isolates of patients treated with abacavir (9,23). However, Y115F does not appear to further diminish the efficiency of incorporation of the NRTI (21).…”
Section: Discussionmentioning
confidence: 96%
“…7,8 Although there is considerable similarity between the two aromatic amino acids, Tyr and Phe, the substitution could still be significant in this case, since studies have shown that this substitution in combination with L74V mutation confers HIV-1 RT resistance against abacavir. 21 Our final model included loops of length 26, 11, and 9 residues, whereas the model of Das et al 7 had corresponding loops of 26 and 23 residues, while Bartholomeuz et al 8 had one long loop of 46 residues. Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…10 and 11). Thus, viral RTs bearing mutations A62V, V75I, F77L, F116Y, and Q151M showed decreased discrimination efficiencies against the triphosphorylated forms of thymidine analogues, such as zidovudine (␤-D-(ϩ)-3Ј-azido-3Ј-deoxythymidine (AZT)) or stavudine (␤-D-(ϩ)-2Ј,3Ј-didehydro-2Ј,3Ј-dideoxythymidine (d4T)), as well as didanosine, zalcitabine, and abacavir (6,12,13). These observations were in agreement with the high level resistance to those inhibitors shown in phenotypic assays by HIV variants carrying those mutations in their RTs (14,15).…”
mentioning
confidence: 99%